ANALISIS JUMLAH INDUSTRI TERHADAP PENYERAPAN TENAGA KERJA DI KABUPATEN SIDOARJO - Tohonan Rohani Silaban; Muhammad Yasin (Maisyatuna, 2025)
This study aims to analyze the relationship between the number of industrial companies, both large-medium and micro-small, with labor absorption in Sidoarjo Regency during the period 2020 to 2023. Sidoarjo Regency, which has a rapidly growing industrial sector, is the location of the study with a focus on the contribution of the industrial sector to reducing unemployment and improving community welfare. The results of the study show that the number of large-medium industrial companies has a significant effect on labor absorption, especially in sectors that require skilled labor. Meanwhile, micro-small industries tend to absorb lower-skilled labor, with most of them in the informal sector. Although there has been an increase in the number of industries, its impact on labor absorption is not always comparable, this is influenced by external factors such as government policies, technological developments, and the quality of the available workforce. Labor absorption also differs by age group, with younger age groups being absorbed more in micro-small industries and older age groups being absorbed more in large-medium industries. This study also shows that sub-districts with better infrastructure have higher labor absorption rates. The suggestion from this research is to improve policies that support equitable industrial development, as well as strengthen skills training programs according to industry needs to increase labor absorption.